Massive Open Online Courses as affinity spaces for connected learning: Exploring effective learning interactions in one massive online community. (March 2018) - Honeychurch, Sarah; Patrick, Fiona
This paper describes a participatory online culture – Connected Learning Massive Open Online Collaboration (CLMOOC) – and asks how its ethos of reciprocity and creative playfulness occurs. By analysing Twitter interactions over a four-week period, we conclude that this is due to the supportive nature of participants, who describe themselves as belonging to, or connected with, the community. We suggest that Gee's concept of an affinity space is an appropriate model for CLMOOC and ask how this might be replicated in a higher education setting.